Genome tuning through HLA and KIR gene clusters impact susceptibility to dengue - Neha Sharma; Gaurav Sharma; Uma Kanga; Devinder Toor (Infectious Medicine, 2023)
Dengue is amongst the most prevalent viral diseases which globally affects millions of individuals annually and renders billions at risk, particularly in tropical and sub-tropical nations. WHO estimated 100–400 million infections each year and reported 4.2 million active cases in 2019 worldwide. The infection is caused by arthropod-transmitted dengue virus which is known to have 5 serotypes (DENV1-5). Most of the cases show mild clinical symptoms; though others may develop severe forms viz; dengue hemorrhagic fever and dengue shock syndrome. Though limited literature suggests the population-specific genetic influence on susceptibility and the clinical course of dengue; the genetic propensity of dengue is largely unknown in most ethnicities. In this context, the human leukocyte antigen (HLA) system represents the most polymorphic region of the human genome and is crucial for the initiation of an appropriate immune response. In most of the genome-wide association studies, the HLA complex is the most significantly linked genetic region with susceptibility or protection towards various infectious and noninfectious diseases. Killer immunoglobulin-like receptors represent another highly variable system present on the surface of natural killer (NK) cells which regulate the activity of NK cells through interactions with their cognate HLA ligands. It is conceivable that the interaction of HLA-Killer immunoglobulin-like receptors systems influences the host susceptibility towards dengue infection as well the disease outcome. Here we attempt to review these parameters in dengue infection and disease outcome. Further detailed investigations are warranted towards the identification of novel susceptibility markers and targeted therapeutic interventions.